The Political Foundations of Economic Crises and the Economic Foundations of Political Crises; The Intermingling Relationship: Turkish Case 1950-2002 - (:unkn) unknown (Kluwer Academic Publishers, 2013)
The political foundations of economic and financial crises have been examined solely vis-à-vis populist macroeconomic policies, but the political consequences of such economic crises have seldom been discussed in the literature. There have been ten notable political crises and six major economic crises in the last half-century of Turkish history. All political crises in Turkey involved a priori economic slowdown. Some of them even followed economic crises, especially sharp devaluations. Secondly, all political crises had social implications, as they all occurred as a result of severe welfare losses of the civilian and military bureaucracy due to inflation. Thirdly, the nature of political crises has recently changed, as they no longer involve overt military interventions. On the contrary, consecutive coups have enhanced the deepening of democracy, as there is a stronger embrace of civil democracy and hostility against the military intentions by the society. Our research demonstrates that all economic crises have occurred during populist right-wing governments and involved budget deficit problems, while only some of them also involved foreign debt crises. Naturally, all economic crises had political consequences. © 2012 International Atlantic Economic Society.
Keywords: Democracy; Economic crises; Emerging market; Political crises